Legal writing - Aquino, David Robert C. (Quezon City : Central Book Supply, 2023)
Thus this revised edition, while keeping true to the original thrust of providing the technical and formal requisites that is manifest of legal writing $1 (BI have taken the liberty of including, as illustrative examples, a cacophony of legal and creative writing that not only accentuates one$1 (Bs arguments and helps one$1 (Bs ideas to come across, but to enhance the communication experience $1 (Bthat of elevating legal writing not only as a rudimentary and necessary skill in the field of law, but as an effective manifestation of creative expression.s
Preliminary Considerations -- Technical Considerations -- Writing Technique -- The Thinking Process -- The Writing Process -- The Writing Output -- Supreme Court Issuances -- Sample Annotations -- Survey of Writing Styles from Jurisprudence.
Keywords: LEGAL WRITING